Wyatt's wagon - Bower, Gary.; Weber, Anthony; Bower, Jan (Wheaton, Ill. : Tyndale House, 2002)
Wyatt learns to include other people in his activities.
"A thinking of others book, book two: including others."
3.0
K-3
Keywords: Friendship -- Fiction; Values -- Fiction; Conduct of life -- Fiction; Friendship -- Fiction; Values -- Fiction; Conduct of life -- Fiction